2015
DOI: 10.23887/jst-undiksha.v1i2.6040
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Mathlet Matematika Eksploratif Untuk Meningkatkan Kompetensi Matematika Siswa SMP Kelas Viii Di Singaraja

Abstract: Penelitian ini adalah penelitian pengembangan yang dimaksudkan untuk meningkatkan kompetensi siswa kelas VIII terhadap konsep-konsep matematika. Pada tahun pertama, beberapa mathlet berhasil dibuat. Mathlet-mathlet tersebut juga telah divalidasi oleh beberapa orang yang kompeten di bidangnya dan juga telah mengalami validasi empirik yang sifatnya terbatas. Pada tahun kedua penelitian dilanjutkan dengan melakukan eksperimen untuk mengetahui pengaruh integrasi mathlet dalam pembelajaran terhadap prestasi belajar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…With the use of manipulative learning media, there is a reciprocal relationship between students and teachers or vice versa. This is supported by the research of Suweken [14] which states that the application of mathlete (GeoGebra) during the learning process makes the level of student involvement in learning improve and the learning achievement of students who are taught by GeoGebra is higher than the achievement of students who are not taught by GeoGebra. Similar results were also found in several studies [15] [16] [17], where from the results of his research it was found that the GeoGebra media-assisted learning device was able to improve student learning activities and students' mathematical communication skills.…”
Section: Discussionmentioning
confidence: 92%
“…With the use of manipulative learning media, there is a reciprocal relationship between students and teachers or vice versa. This is supported by the research of Suweken [14] which states that the application of mathlete (GeoGebra) during the learning process makes the level of student involvement in learning improve and the learning achievement of students who are taught by GeoGebra is higher than the achievement of students who are not taught by GeoGebra. Similar results were also found in several studies [15] [16] [17], where from the results of his research it was found that the GeoGebra media-assisted learning device was able to improve student learning activities and students' mathematical communication skills.…”
Section: Discussionmentioning
confidence: 92%
“…Dengan adanya penggunaan media pembelajaran manipulatif terjadi hubungan timbal balik antara siswa dan guru ataupun sebaliknya. Hal ini didukung oleh penelitian Suweken (2011) yang menyatakan bahwa dengan diterapkannya mathlet (GeoGebra) selama proses pembelajaran membuat tingkat keterlibatan siswa dalam pembelajaran menjadi membaik serta prestasi belajar siswa yang dibelajarkan dengan GeoGebra lebih tinggi dari prestasi siswa yang tidak dibelajarkan dengan GeoGebra. Hasil yang serupa juga ditemukan oleh beberpa penelitian (Putrawan, 2014;Supriadi, 2015;Nopiyani, Turmudi & Prabawanto, 2016), dimana dari hasil penelitiannya diperoleh bahwa perangkat pembelajaran berbantuan media GeoGebra mampu meningkatkan aktivitas belajar siswa dan kemampuan komunikasi matematis siswa.…”
Section: Pembahasanunclassified
“…In secondary school, the use of mathlet has been successful in improving students' understanding about the concept of position of two lines. In the research by [3], the following mathlet ( Fig. 5) had been used to improve students understanding about gradient of lines and their relationship to position of two lines.…”
Section: The Use Of Geogebra Mathlet In Learning Mathematicsmentioning
confidence: 99%